Estruturação do sistema de gestão ambiental a partir do sistema de gestão de qualidade para uma empresa do ramo de confecções - Brendler, Elói (2009)
The constant preoccupation with process and product of quality generated in the companies a search for certifications aimed the continuous improvement. The certifications ISO 9001 and ISO 14001 are among the most demanded. The first search a system of quality management and the focus on customer needs. The second is worried about the environmental management systems and the needs of stakeholders and the crescent needs of society on environmental protection. This study investigated to structure an Environmental Management System from the System of Quality Management to a company in the clothing. This organization was founded in 1989, with over 700 employees, and is presently in the final stages of implementation of ISO 9001:2000. This study used the technique of exploratory and descriptive. It is a case study with method of action research. The study describes the current phase of implementation of ISO 9001:2000 in the company and its contribution to the environmental management system. The maker identified the internal processes and environmental aspects and potential environmental impacts. After, the study structured environmental management system appropriate to the company, and analyze the implementation of ISO 9001:2000 and ISO 14001:2004 in an integrated manner. In the finalization this study related the advantages and disadvantages of this integration of standards